1996
DOI: 10.4269/ajtmh.1996.54.511
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-Mouthed Water Storage Vessels and in Situ Chlorination in a Bolivian Community: A Simple Method to Improve Drinking Water Quality

Abstract: Abstract. Epidemiologic investigations of the Latin America cholera epidemic have repeatedly implicated untreated drinking water and water touched by hands during storage as important vehicles for disease transmission. To prevent such transmission, we provided a new narrow-mouthed, plastic, water storage vessel and 5% calcium hypochlorite solution for home disinfection of stored water to a Bolivian Aymara Indian community at risk for cholera. We evaluated acceptance of this intervention and its effect on water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 15 publications
6
57
0
Order By: Relevance
“…A short-term alternative involves the use of a narrow-necked water container with spout and chemical disinfectant, such as that used in this and other studies. [14][15][16] Our data suggest that this simple combination of water disinfection and a physical barrier to recontamination, if used appropriately and supplemented with hygiene education, can be an affordable, effective short-term means of reducing diarrheal rates in those areas where potable water is currently not available. Our study not only documents the feasibility and effectiveness of this method but also establishes the behavioral and cultural willingness of our study population to adopt such an intervention, provided the containers are made available.…”
Section: Discussionmentioning
confidence: 99%
“…A short-term alternative involves the use of a narrow-necked water container with spout and chemical disinfectant, such as that used in this and other studies. [14][15][16] Our data suggest that this simple combination of water disinfection and a physical barrier to recontamination, if used appropriately and supplemented with hygiene education, can be an affordable, effective short-term means of reducing diarrheal rates in those areas where potable water is currently not available. Our study not only documents the feasibility and effectiveness of this method but also establishes the behavioral and cultural willingness of our study population to adopt such an intervention, provided the containers are made available.…”
Section: Discussionmentioning
confidence: 99%
“…These lessons from the pre-antibiotic era should not be forgotten; in addition to the promotion of ORS as the mainstay of treating clinical cases of cholera, public health efforts should focus on bringing safe, reliable drinking water to regions such as Asembo. Point-of-use chlorination programs and safe water storage containers are an inexpensive approach 19,20 that can be rapidly implemented. More permanent measures are the construction of water-and sewage-treatment facilities.…”
Section: Discussionmentioning
confidence: 99%
“…risk of diarrhoea through treatment of water with sodium hypochlorite solution, safe water storage, and behaviour change techniques (Luby, 2004;Semenza, 1998;Quick, 1996Quick, , 2002. A recent study in Uganda demonstrated that use of the SWS reduced the number of episodes and duration of diarrhoea among people with HIV .…”
Section: Introductionmentioning
confidence: 99%